Answer:
2x^2 - 8x + 6
Step-by-step explanation:
2x*x+(-3x*2x)+(x*(-2))+6=
2x^2-8x+6
Answer:
49.5 mi
Step-by-step explanation:
Area of a triangle is A = (height) X (base) / 2
So if you plug in the numbers you get:
806.9 = (32.6) X (base) / 2
1613.8 = (32.6) X (base)
1613.8 / 32.6 = base
base = 49.5 mi
Answer:
34.5 units
Step-by-step explanation:
Divide the composite figure into different shapes and then find the areas of all the shapes and add them together to find the total area. We could divide this into 3 triangles and 1 rectangle.
Answer:-12, -10, -3.5, 6, 11
Step-by-step explanation: